Roles of 5-Lipoxygenase and Cysteinyl-Leukotriene Type 1 Receptors in the Hematological Response to Allergen Challenge and Its Prevention by Diethylcarbamazine in a Murine Model of Asthma - Masid-de-Brito, Daniela; Queto, Túlio; Gaspar-Elsas, Maria Ignez C.; Xavier-Elsas, Pedro (Mediators of Inflammation, 2014)
Diethylcarbamazine (DEC), which blocks leukotriene production, abolishes the challenge-induced increase in eosinopoiesis in bone-marrow from ovalbumin- (OVA-) sensitized mice, suggesting that 5-lipoxygenase (5-LO) products contribute to the hematological responses in experimental asthma models. We explored the relationship between 5-LO, central and peripheral eosinophilia, and effectiveness of DEC, using PAS or BALB/c mice and 5-LO-deficient mutants. We quantified eosinophil numbers in freshly harvested or cultured bone-marrow, peritoneal lavage fluid, and spleen, with or without administration of leukotriene generation inhibitors (DEC and MK886) and cisteinyl-leukotriene type I receptor antagonist (montelukast). The increase in eosinophil numbers in bone-marrow, observed in sensitized/challenged wild-type mice, was abolished by MK886 and DEC pretreatment. In ALOX mutants, by contrast, there was no increase in bone-marrow eosinophil counts, nor in eosinophil production in culture, in response to sensitization/challenge. In sensitized/challenged ALOX mice, challenge-induced migration of eosinophils to the peritoneal cavity was significantly reduced relative to the wild-type PAS controls. DEC was ineffective in ALOX mice, as expected from a mechanism of action dependent on 5-LO. In BALB/c mice, challenge significantly increased spleen eosinophil numbers and DEC treatment prevented this increase. Overall, 5-LO appears as indispensable to the systemic hematological response to allergen challenge, as well as to the effectiveness of DEC.